2017
DOI: 10.1111/add.14033
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of concentrated naloxone nasal spray for opioid overdose reversal: Phase I healthy volunteer study

Abstract: Background and AimsTake‐home naloxone can prevent death from heroin/opioid overdose, but pre‐provision is difficult because naloxone is usually given by injection. Non‐injectable alternatives, including naloxone nasal sprays, are currently being developed. To be effective, the intranasal (i.n.) spray dose must be adequate but not excessive, and early absorption must be comparable to intramuscular (i.m.) injection. We report on the pharmacokinetics (PK) of a specially produced concentrated novel nasal spray. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
74
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 21 publications
4
74
1
3
Order By: Relevance
“…The standard mode of administration for naloxone is intravenously (IV) but, in an effort to make it more accessible, Sir John Strang worked with a team to produce an intranasal version that was compared with iv and intramuscular (IM) versions. 2 Results showed that IV administration of naloxone (0.4mg) produces a 'big spike' in mean plasma concentration, throwing the patient immediately into withdrawal symptoms, which is why ambulance crews now administer IM naloxone (0.4mg) to avoid an aggressive spike but ensure similar recovery. The onset of action of intranasal naloxone at a 1mg dose was not immediate enough for use in the emergency care setting, while the 4mg intranasal dose produced a 'big spike' in mean plasma concentration that resulted in withdrawal symptoms.…”
mentioning
confidence: 99%
“…The standard mode of administration for naloxone is intravenously (IV) but, in an effort to make it more accessible, Sir John Strang worked with a team to produce an intranasal version that was compared with iv and intramuscular (IM) versions. 2 Results showed that IV administration of naloxone (0.4mg) produces a 'big spike' in mean plasma concentration, throwing the patient immediately into withdrawal symptoms, which is why ambulance crews now administer IM naloxone (0.4mg) to avoid an aggressive spike but ensure similar recovery. The onset of action of intranasal naloxone at a 1mg dose was not immediate enough for use in the emergency care setting, while the 4mg intranasal dose produced a 'big spike' in mean plasma concentration that resulted in withdrawal symptoms.…”
mentioning
confidence: 99%
“…
Commentary on McDonald et al (2018): Intranasal naloxone-from the laboratory to the real world It is timely that research and technology combine to develop products addressing barriers to naloxone administration in community and prison settings. Addressing potential implementation barriers and understanding outcomes with real-world use will maximize the opportunities to prevent opioid overdose deaths.

The work by McDonald and colleagues [1] is a welcome addition to what is known about naloxone bioavailability and pharmacokinetics, combined with the promise of a fit-for-purpose naloxone product for lay-person administration.

…”
mentioning
confidence: 99%
“…Addressing potential implementation barriers and understanding outcomes with real-world use will maximize the opportunities to prevent opioid overdose deaths.The work by McDonald and colleagues [1] is a welcome addition to what is known about naloxone bioavailability and pharmacokinetics, combined with the promise of a fit-for-purpose naloxone product for lay-person administration. Intranasal and other non-injectable naloxone formulations have clear benefits for community supply to carers and family members.…”
mentioning
confidence: 99%
See 2 more Smart Citations